Prominent Perspective on Existing Biological Hallmarks of Alzheimer’s Disease - Singh, Namrata; Sharma, Srishti; Ghosh, Kallol K.; Gupta, Bhanushree; Kuca, Kamil (Current Topics in Medicinal Chemistry, 2024)
Biomarkers are the most significant diagnosis tools tending towards unique approaches and solutions for the prevention and cure of Alzheimer’s Disease (AD). The current report provides a clear perception of the concept of various biomarkers and their prominent features through analysis to provide a possible solution for the inhibition of events in AD. Scientists around the world truly believe that crucial hallmarks can serve as critical tools in the early diagnosis, cure, and prevention, as well as the future of medicine. The awareness and understanding of such biomarkers would provide solutions to the puzzled mechanism of this neuronal disorder. Some of the argued biomarkers in the present article are still in an experimental phase as they need to undergo specific clinical trials before they can be considered for treatment.
Keywords: tau protein